Customs related to childbirth in the Matsigenka indigenous community of Camisea, Cusco, Peru - Araujo Salas, Brenda Liz (2018)
The introduction of Western medicine through public health programs and new medical centers in many regions, especially in rural areas, has generated conflict between local traditional practitioners and Western modes of care, specifically around pregnancy and childbirth. This in turn, has generated a general devaluing of traditional practices of healthcare, and the degradation and discrediting of traditional healers and midwives. This article aims to describe the customs related to childbirth that Matsigenka women in the native community of Camisea currently practice. Additionally, this article looks at what is taught to a young woman during her first menstruation, care during the pregnancy and postpartum periods; finally explains the relationship of the Matisgenka women of the Camisea community with the public health system.